Kinerja Pelabuhan Konvensional di Makassar - Prakasa Eko Wibowo; D.A Lasse; Sulistyawati Toelle (Jurnal Manajemen Transportasi & Logistik (JMTRANSLOG), 2019)
The purpose of the paper is to find out the effect of loading unloading and clearance in/out service preparation of the loading unloading productivity to the performance of Makassar Conventional Port. The problem of the paper was the low performance of loading unloading productivity in Makassar Conventional Port due to nature resources, facilities, and human resources. The paper used quantitative method using path analysis. There were 60 samples taken. The result of the paper partially shows that there is a significant and direct effect of loading unloading productivity to the port performance of general cargo ships in Makassar Conventional Port.